A Randomized Clinical Trial Comparing the ELLIPTA and HandiHaler Dry Powder Inhalers in Patients With COPD: Inhaler-Specific Attributes and Overall Patient Preference. (2nd January 2018) - Collison, Kathryn A; Patel, Pinal; Preece, Andrew F; Stanford, Richard H; Sharma, Raj K; Feldman, Gregory
ABSTRACT: This randomised, open-label, cross-over, placebo-containing inhaler study assessed patient preference indicators for ELLIPTA and HandiHaler dry powder inhalers in patients with COPD (NCT02786927; GSK identifier: 204983). The primary objective of this study was to assess patient preference between ELLIPTA and HandiHaler based on the number of steps needed to use the inhaler. Eligible patients ≥40 years of age with COPD were randomised 1:1 to receive their current COPD medication plus a placebo-containing ELLIPTA or HandiHaler inhaler once daily for 7 ± 2 days (treatment period 1); this was followed by a 7 ± 2-day placebo treatment with the alternative inhaler. A 5-item questionnaire assessed inhaler-related patient preferences. A total of 212 patients (mean age, 65.1 years) were enrolled at 22 US sites; 73% had a COPD duration ≥5 years. Median (range) exposure was 8 (5, 13 ) days for ELLIPTA and 8 (1, 16) days for HandiHaler. Significantly more patients preferred ELLIPTA to HandiHaler in terms of the number of steps to use and all secondary attributes (size, comfort of the mouthpiece, remaining doses, and ease of use of the two inhalers; all p < 0.001). Similar results were observed irrespective of the order of inhaler use. Eighteen patients (8%) reported at least one AE and two (<1%) patients reported four non-fatal SAEs; none were related to the study treatment. Patient attitude toward a particular inhaler and their experiences in using it can affect adherence to therapy, which can in turn strongly influence effectiveness of inhaled medications. This study uses a robust methodology to assess patient preference.